Be aware of how COVID‐19 could impact international students - Hope, Joan (Enrollment Management Report, 2020)
The spread of COVID‐19 has impacted every aspect of college and university operations — and life in general. As you look ahead, consider ways the pandemic could impact your current and potential international students so you can implement plans to address the challenges.